‘Igal’ ritual theatre: ‘High-Value Culture’ from DAKEN21 and Malaysia MADANI perspectives - Mohd Kipli Abdul Rahman; Norzizi Zulkafli; Sharifuddin Zainal; Abdullah Hayeesaid (ResearchGate, 2024)
This paper explores the igal ritual theatre practised by the Bajau ethnic group in Sabah, Malaysia, that is performed to heal for the community's well-being and focuses on the concept of high-value culture, which goes hand in hand with the thrust of 'Malaysia MADANI' and National Cultural Policy 2021 (DAKEN21). The ethnographic method is applied through an 'inductive phenomenological character' approach involving descriptive research design exploration and case studies. The relationship of six igal ritual theatre elements and their meaning, high-value culture, and the concept of 'Malaysia Madani' is highlighted to demonstrate the community's well-being and ensure the quality of life